Poly[(μ2-4,4′-bipyridine-κ2N:N′)(μ2-2,2-dimethylcyclopentane-1,3-dicarboxylato-κ4O1,O1′:O3,O3′)cadmium] - Zhang, Xian-Fa; Gao, Shan; Ng, Seik Weng (International Union of Crystallography, 2011)
In the title polymeric compound, [Cd(C9H12O 4)(C10H8N2)]n, the CdII atom is located on a twofold rotation axis and is coordinated by two 4,4′-bipyridine ligands and two 2,2-dimethylcyclopentane-1,3- dicarboxylate ions. The carboxylate ion and the N-heterocycle both function as bridges to link adjacent CdII atoms to result in the formation of a layer structure parallel to (010). The mid-point of the central C - C bond of the 4,4′-bipyridine ligand is located on an inversion center. In the crystal, the carboxylate ion is disordered over a twofold rotation axis in respect of its methyl group and the cyclo-pentane ring. © Zhang et al. 2011.